A Systematic Review on Traditional Medicinal Plants Used for the Treatment of Viral and Fungal Infections in Ethiopia - Aschale Y; Wubetu M; Abebaw A; Yirga T; Minwuyelet A; Toru M (Dove Medical Press, 2021)
Yibeltal Aschale,1 Muluken Wubetu,2 Abtie Abebaw,1 Tadesse Yirga,3 Awoke Minwuyelet,4 Milkiyas Toru1 1Department of Medical Laboratory Sciences, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 2Department of Pharmacy, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 3Department of Pediatrics & Child Health Nursing, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 4Bichena Primary Hospital, Bichena, EthiopiaCorrespondence: Milkiyas ToruDepartment of Medical Laboratory Sciences, College of Health Sciences, Debre Markos University, PO Box 269, Debre Markos, EthiopiaTel +251940631035Email milkiastoru@gmail.comBackground: Traditional medicine is still playing an important role in meeting the basic health care requirement of the peoples in different parts of Ethiopia. There is no published review that clearly indicates documented medicinal plants available in different parts of the country used for treating viral and fungal infections. Currently, viral epidemics with high mortality and morbidity like SARS COV-2 are emerging. Screening of promising drug from plant source is vital to control such viral and fungal infections. In addition, indicating the most commonly used parts of the plant and their route of administration will help for further drug formulation studies. This review aimed to present an indication of the ethnomedicinal plants used for the treatment of fungal and viral infections.Methods: The databases (Google Scholar, pub med, hinari, and research gate) were searched for published articles on the ethnobotany of medicinal plants used to treat viral and fungal infection in Ethiopia without restriction in the methodology and year of publication. Viral infections, fungal infections, anti-fungal and anti-viral activity, ethnobotany, Ethiopia, and medicinal plants were the key search terms. Studies that did not have complete ethnobotanical data and did not address viral and fungal infection as a disease treated traditionally by the practitioners were excluded.Results: A total of 249 articles were produced by database search. After amendment for exclusion criteria and duplicates, 15 articles were found appropriate for the review. The majority of the studies were qualitative and others were mixed type in nature. All of the medicinal plants traditionally used to treat viral and fungal infections in Ethiopia were not scientifically confirmed. Out of the 95 identified plants, 40.8% were herbs and from the plant parts used and 43.9% and 21.1% were leaves and roots, respectively. The majority, (48.8%), of the plant remedies were given orally. Rabies and Tinea capitis constitute the highest percentage of viral and fungal infections treated by traditional medicinal plants followed by hepatitis and Tinea corporis, respectively.Conclusion: Various plants have been used to treat viral and fungal infections. Information obtained from this review serves as a guide to discover novel antiviral and antifungal agents from plants. Therefore, it is advisable for field researchers to properly identify, document, conserve and conduct efficacy and safety studies on such medicinal plants in animal models.Keywords: review, traditional medicine, ethnobotany, viral and fungal infection